Climate change impacts and greenhouse gas mitigation effects on U.S. hydropower generation. (1st December 2016) - Boehlert, Brent; Strzepek, Kenneth M.; Gebretsadik, Yohannes; Swanson, Richard; McCluskey, Alyssa; Neumann, James E.; McFarland, James; Martinich, Jeremy
Highlights: Analyze contiguous U.S. hydropower generation under various emissions scenarios. Employ systems model that allocates water to competing uses in 2119 river basins. Average U.S. generation increases under climate change, but falls under low flows. Mitigation benefits are 2-4 billion/year due to high values of carbon-free energy. Abstract: Climate change will have potentially significant effects on hydropower generation due to changes in the magnitude and seasonality of river runoff and increases in reservoir evaporation. These physical impacts will in turn have economic consequences through both producer revenues and consumer expenditures. We analyze the physical and economic effects of changes in hydropower generation for the contiguous U.S. in futures with and without global-scale greenhouse gas (GHG) mitigation, and across patterns from 18 General Circulation Models. Using a monthly water resources systems model of 2119 river basins that routes simulated river runoff through reservoirs, and allocates water to potentially conflicting and climate dependent demands, we provide a first-order estimate of the impacts of various projected emissions outcomes on hydropower generation, and monetize these impacts using outputs from an electric sector planning model for over 500 of the largest U.S. hydropower facilities. We find that, due to generally increasing river runoff under higher emissions scenarios in the Pacific Northwest, climate change tends to increase overall hydropower generation in the contiguous U.S. During low flow months, generation tends to fall with increasing emissions, potentially threatening the estimated low flow, firm energy from hydropower. Although global GHG mitigation slows the growth in hydropower generation, the higher value placed on carbon-free hydropower leads to annual economic benefits ranging from 1.8 billion to 4.3 billion. The present value of these benefits to the U.S. from global greenhouse gas mitigation, discounted at 3%, is 34 to 45 billion over the 2015–2050 period.